1973
DOI: 10.1111/j.2042-7158.1973.tb09108.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the thermodynamics of the methyl group in solutions of drug molecules

Abstract: The contribution of the CH, group to the solution thermodynamics of drug molecules is dependent on whether it is attached to a ring system or is in the terminal position in an aliphatic chain. In the former case group contributions for CH, are very similar to those found for the CH2 group. For instance, in partition, the CH, group contribution (log FCH,) is in the range 0.65 to 0.28 (AG = 2.303 RT log FCHJ and is dependent on the polarity of the organic solvent. The contribution for the terminal aliphatic CH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 53 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…For the ester group contribution the two lines have similar gradients (measured [1É16, SD \ 0É08 ; predicted [1É29, SD \ 0É03) but the measured set shows no signiÐcant di †erence for points at 0É5, 5, 10 and 17% ethanol (v/v). The energy contribution of the ester group at 0É5% (v/v) ethanol was calculated to be 6500 Jmol~1, but as calculated this included a correction factor for the end methyl group (Davis 1973a). A mean correction value of 4770 Jmol~1 was obtained from alkane solubility and was considered valid for partition studies provided that they involved reasonably non-polar solvents.…”
Section: Relationships Between Activity Coefficient and Ester Chain Lmentioning
confidence: 99%
“…For the ester group contribution the two lines have similar gradients (measured [1É16, SD \ 0É08 ; predicted [1É29, SD \ 0É03) but the measured set shows no signiÐcant di †erence for points at 0É5, 5, 10 and 17% ethanol (v/v). The energy contribution of the ester group at 0É5% (v/v) ethanol was calculated to be 6500 Jmol~1, but as calculated this included a correction factor for the end methyl group (Davis 1973a). A mean correction value of 4770 Jmol~1 was obtained from alkane solubility and was considered valid for partition studies provided that they involved reasonably non-polar solvents.…”
Section: Relationships Between Activity Coefficient and Ester Chain Lmentioning
confidence: 99%
“…Shanbhag and Axelsson (1975) suggested measuring hydrophobic interactions of proteins in aqueous environments by using aqueous two-phase partitioning. Zaslavsky et al (1978Zaslavsky et al ( , 1981Zaslavsky et al ( , 1984 suggested that the hydrophobic properties of aqueous two-phase systems could be quantified by the use of a AGCH2 value (Davis et al, 1972), which is the free energy of methylene group transfer between the phases. This free energy is a measure of the difference in partition coefficients in a homologous series of compounds between solutes differing in one chain length Both previous studies of peptide partitioning used the PEG/dextran system with an added buffer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they were estimated using the measured value for the unsubstituted compound, p-methylhippuric acid, and the functional group contributions obtained from the bulk solvent/water partition coefficients measured in the p-toluic acid series. The independence of functional group contributions to transfer free energies in bulk solvents is well established (4,5). The values for 4 bulk organic solvent/water systems (hexadecane, hexadecene, 1,9-decadiene, and 1-octanol) are shown in Table 1.…”
Section: Functional Group Contributions To the Standard Free Energy Omentioning
confidence: 99%
“…There is abundant evidence that the independence and additivity of functional group contributions can generally be assumed for bulk phase transfer free energies as determined from organic solvent/water partition coefficients (4,5), provided that appropriate nonadditivity corrections are made to account for chain branching or other steric factors, electronic effects, intramolecular hydrogen-bonding, etc. (6).…”
Section: Introductionmentioning
confidence: 99%